Paleokarst : a systematic and regional review - Bosak, Pavel; Ford, Derek (Derek C.); Gazek, Jerzy; Horacek, Ivan (Developments in earth surface processes, 1989)
Prepared by some of the world's leading experts in the field, this book is the first summarizing work on the origin, importance and exploitation of paleokarst. It offers an extensive regional survey, mainly concerning the Northern Hemisphere, as well as a thorough analysis of the problems of research into paleokarst phenomena, with particular emphasis on theoretical contributions and practical exploitation. By concentrating on phenomena which have appeared in the course of geological history, the book represents a substantial development in the general theory of paleokarst and demonstrates the advantages of a comprehensive approach to the problem. Considerable emphasis is put on the economic importance of paleokarst phenomena, from the point of view of exploiting significant deposits of mineral raw materials, as well as from a civil engineering and hydrological point of view. Since the publication deals with a boundary scientific discipline, it is intended for specialists from various branches of science: geologists, paleontologists, economic geologists, geographers, mining engineers and hydrogeologists.